Application of machine learning techniques on the context of predicting upcoming traffic congestion and providing the best preferred path - Saquib, Muhammad Sadman; Ali, Mili Mohammad; Tazmim, Marisha; Ahmad, Faiyaaz (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.